Digitally Post-Human: Living On and After. Issue 1 (April 2020) - Wood, Nigel
Abstract : Definitions of digital abound at the present time, but there is a thread amongst the most vital of these that questions the relevance of human agency and evaluative choice. If we follow where technological advances take us we come to the unsettling conclusion that 'machine reading' has usurped more analogue procedures and that algorithmic formulae have supplanted human judgement; the opportunities that new software provide can outstrip our imagination in framing research questions. Literary history, however, addresses how we might make sense of the One as well as the Many, and, when confronted by a string of word- or phrase-patterns, it is not that our findings speak for themselves; we have to conjure their value. This is exemplified by analysing where some digital searches might take us in relation to Shakespeare's The Merchant of Venice, basing the reading on all the repetitions of gentile / gentle, kind, and credit . The sensitive interrogation of the play's electronic text does point us to salient 'returns' and patterning signalled by following where the significant iterations of these words might take us, but what we make of these lines of enquiry eventually calls on human evaluation and volition.